MORALITY AND HUMAN RESPONSIBILITY IN THE PERSPECTIVE OF MURTADHA MUTHAHHARI'S ETHICS - Purnamasari, Elvira; Aprilianti, Dika (Al-Imtaz: Jurnal Keilmuan Ushuluddin, 2024)
This article explores the ethical thought of Murtadha Muthahhari, a 20th century Islamic scholar from Iran. The study aims to explore Muthahhari's views on morality and human responsibility, which form the basis of ethical behavior in social and religious contexts. Using qualitative research methods and text analysis, the study found that Muthahhari viewed ethics as a fundamental foundation for the formation of civilized and responsible human behavior. He emphasizes the importance of self-awareness as the first step to understanding true morality, which is aligned with the values of faith. The study also shows the relevance of Muthahhari's thought to contemporary moral challenges, particularly in building a just and moral society. By emphasizing the close relationship between faith, reason, and social responsibility, this study provides a deep insight into how Islamic values can be applied in the face of the complexities of modern life.